Pengaruh Motivasi Kerja, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Unex Rajawali Indonesia - Nickya Damayanti (2021)
This research is a quantitative research which aims to s determine the magnitude of the influence between work motivations, work discipline and work environment on employee performance. The study uses a sample size of 79 respondent, which are part of the population of PT Unex Rajawali Indonesia, the sampling technique is probability sampling with random sampling method.. The analysis techniqal used in this study is the validity test, reliability test, coefficient of determination, f test, and t tets with a significant level of 5% (0,05). Stated from the test results that: (1) work motivation has a significant effect on employee performance with a t value of 5,021 > t tabel 1,992 (2) work discipline has a significant effect on employee performance with a t value of 4,976 > t tabel 1,992 (3) work environment has a significant effect on employee performance with a t value of 2,860 > t tabel 1,992 (4)simultaneously work motivation, work discipline and work environment have a significant effect on employee performance with a calculated f value of 81,409 > f tabel 2,72 and has an R square value of 76,5%.